Europe and Central Asia's Great Post-Communist Social Health Insurance Experiment : Impacts on Health Sector and Labor Market Outcomes - Wagstaff, Adam; Moreno-Serra, Rodrigo (World Bank, Washington, DC, 2012)
The post-communist transition to social health insurance in many of the Central and Eastern European and Central Asian countries provides a unique opportunity to try to answer some of the unresolved issues in the debate over the relative merits of social health insurance and tax-financed health systems. This paper employs a regression-based generalization of the difference-in-differences method and instrumental variables on panel data from 28 countries for the period 1990-2004. The authors find that, controlling for any concurrent provider payment reforms, adoption of social health insurance increased national health spending and hospital activity rates, but did not lead to better health outcomes. The authors also find that adoption of social health insurance reduced employment in the economy as a whole and increased unemployment, although it did not apparently increase the size of the informal economy.